The Challenges Of Institutional Actors: Study On The Management And Distribution Of Conditional Cash Transfer Program in Banjarmasin - Aliy Arivin Anward; Isbandi Rukminto Adi (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to study the challenges faced by actors in management and distribution of CCT. There has been no research the challenges faced by actors in management and distribution of CCT program during the 2020-2021 COVID-19 period and there has been no research regarding the analysis of challenges faced by actors in management and distribution of CCT. The research adopts a qualitative approach, involving basic research and descriptive research to build/test theories and describe the challenges faced by actors in the CCT Program. Study findings related to this research identified three actor challenges. The first challenge concerns the passive role of institutions and the number of human resources in CCT distribution. The second challenge involves delays in funds and beneficiary data, as well as data accuracy issues, such as beneficiary family addresses, National Identify Number (NIN), and marital status. The third challenge pertains to protests from the community and administrative negligence by the community. The study concludes with three actor challenges in the CCT program's target inaccuracies: human resources, data, and community.